Pengaruh Earning Per Share, Debt To Equity Ratio, Price Earning Ratio, Return On Equity Terhadap Harga Saham Perusahaan Makanan Dan Minuman Di Bei Periode 2015-2017 - Indrian Trifena Suriadi dan Indra Widjaja (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine the effect of financial performance on stock returns in food and beverage companies listed on the Indonesia Stock Exchange in 2015 to 2017 simultaneously or partially. The variables used in this study are Earning Per Share (EPS), Debt To Equity Ratio (DER), Price Earning Ratio (PER), Return On Equity (ROE) as independent variables and stock return as the dependent variable.  The data used are financial statements from food and beverage companies published through the website ww.idx.co.id. The results of the study show that the independent variables EPS, DER, PER, ROE do not significantly influence the dependent variable (stock return) simultaneously. While the results of the study are partial, it shows that only EPS and ROE variables have a significant effect on stock returns. Thus it can be concluded that all the independent variables studied cannot be used simultaneously to determine the amount of stock returns. The data analysis method used in this study is a quantitative method by testing classical assumptions, as well as statistical analysis, namely multiple linear regression analysis. The sampling method used was purposive sampling.